PARADIGMA FILSAFAT EKONOMI SYARIAH SEBAGAI SUATU SOLUSI KEHIDUPAN MANUSIA - Ghozali, Mohammad; Sari, Tryas Titi (DIKTUM: Jurnal Syariah dan Hukum, 2018)
The philosophy of Economics Sharia or Islamic real economics have appeared since the existence of the religion of Islam, i.e. Since the days of the Prophet. His goal was to bring humans to the world and the hereafter fallah and putting human beings as the Caliph was given a treasure by God to take advantage of what is on Earth with his best. A Socialist or a capitalist system is not able to answer the problem humans with leaves many problems of life, with evidence that the system is not able to give welfare to humanity as a whole even just for some particular people only. This factor becomes one evidence that economy more Islamic have the right concept and can provide overall well-being to mankind. It can be seen from the deployment of Islamic economic system since the days of the Prophet, which has provided a good impact to the society that existed at the time. And when the system is taken down to the next generation, in fact it can be applied with good and provide solutions for existing problems. Thus Islamic economic philosophy is holding an important role in the development of the economy of humans for the sake of reaching fallah is expected.